A review on the use of medicinal plants in the treatment and prevention of COVID-19 (Research, Society and Development, 2022)
The use of medicinal plants with therapeutic purpose, for the treatment, prevention and cure of diseases has been used by humanity since the beginning of time, during the period of facing the pandemic of COVID-19, several peoples have resorted to empirical and traditional knowledge associated with the use of medicinal plants. This is a Systematic Review of Literature, where data collection takes place virtually, searching for articles in the databases Google Academic, Virtual Health Library (VHL) and Scientific Electronic Library Online (SCIELO), Revista Brasileira de Plantas Medicinais and Revista de Farmacognosia, with the following descriptors: in Health Sciences (DeCS): "medicinal plants" AND "COVID-19" AND "SARS-CoV-2" AND "Coronavirus". For data collection and analysis, there was a process and flow to concentrate articles related to the main theme of the research and to evidence the findings. The main plants found for the treatment and/or prevention of COVID-19 were: Guaco (Mikania glomerata. Sprengel), Quina-quina (Coutarea hexandra Schum), Jatobá (Hymenaea courbaril), Broccoli (Brassica oleracea), Boldo (Pneumus boldus), Chamomile (Matricariare Mint (Menthacitrata Ehrh), Orange (Citrusaurantium L.), Garlic (Alliumsativum), Passion Fruit (Passiflora alata Curtis.Passiflora incarnata L.), Cider (Cymbopogoncitratus.), Although I use it. Although the available studies offer several indications that these plant-derived products may help fight COVID-19, further studies should be conducted to assess the clinical usefulness of these products against COVID-19 infection.